Case Report: Kawasaki disease associated with acute generalized exanthematous pustulosis secondary to carbocysteine - Furuta, Takashi; Fukumoto, Hiroyuki; Fujiwara, Mayu; Fukunaga, Shinnosuke; Ishikawa, Yuichi; Hirano, Reiji (Frontiers in Pediatrics, 2024)
Acute generalized exanthematous pustulosis (AGEP) is an uncommon eruption characterized by sterile pustules on an erythematous background, which is usually associated with drugs. AGEP is described as a self-limiting disease with favorable prognosis. We reported a case of Kawasaki Disease (KD) following AGEP. A 3-year-old male, who was admitted with pustules and five days of fever at our hospital, was diagnosed with AGEP. Despite the skin lesions and fever improving drastically after prednisolone therapy, the fever recurred on hospitalization day 5. The following symptoms suggestive of KD also appeared: bulbar conjunctival hyperemia, cervical lymphadenopathy, erythema of the lips, eruption on his trunk, and erythema and edema of the hands and feet. He was diagnosed with KD and treated with intravenous immunoglobulin. He was discharged on the thirteenth day of hospitalization without cardiac complications. Drug-induced lymphocyte stimulation test revealed carbocysteine as the suspected cause of AGEP, which consequently triggered KD. Because a mucosal lesion is uncommon in AGEP, bulbar conjunctival hyperemia suggested that KD sequentially occurred after AGEP. Since AGEP is benign and self-limited in most cases, it is necessary to differentiate other diseases, including KD, when recurrent fever or rash occurs in the course of AGEP.